Thermodynamics’ third law and quantum phase transitions - Kruse, M. K. G. (2010)
We report on the fact that microscopically enforcing fulfillment of thermodynamics' third law on a system of fermions automatically yields the values of the external parameter (here coupling strengths in the pertinent Hamiltonian) at which quantum phase transitions take place. Our considerations are illustrated via an exactly solvable model of Plastino and Moszkowski [Il Nuovo Cimento 47, 470 (1978)].